2003
DOI: 10.1046/j.1365-8711.2003.07036.x
|View full text |Cite
|
Sign up to set email alerts
|

Elusive active galactic nuclei

Abstract: A fraction of active galactic nuclei do not show the classical Seyfert‐type signatures in their optical spectra, i.e. they are optically ‘elusive’. X‐ray observations are an optimal tool to identify this class of objects. We combine new Chandra observations with archival X‐ray data in order to obtain a first estimate of the fraction of elusive active galactic nuclei (AGN) in local galaxies and to constrain their nature. Our results suggest that elusive AGN have a local density comparable to or even higher than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 41 publications
4
157
0
Order By: Relevance
“…Large amounts of OH can be formed through dissociative recombination of H 3 O + , which in turn is formed through the sequence O + → OH + → H 2 O + → H 3 O + (Maloney et al 1996); as we will report in a forthcoming paper, these molecular ions are indeed detected in absorption from excited levels in both sources. However, both NGC 4418 and Arp 220 have strong X-ray deficits relative to the FIR emission (Maiolino et al 2003;Iwasawa et al 2005). From the X-ray flux reported by Maiolino et al (2003) from NGC 4418, F X (0.3−8 keV) = 1.5 erg s −1 cm −2 , and assuming a point-like X-ray source located at the center of our C core component, the X-ray flux at the surface of C core (r ∼ 10 pc) is ∼0.1 erg s −1 cm −2 ; a similar estimate for Arp 220 with the fluxes reported by Iwasawa et al (2001) yields an X-ray (0.5−10 keV) flux at the surface of the western nucleus (r ∼ 50 pc) of ∼0.5 erg s −1 cm −2 .…”
Section: X-and Cosmic Raysmentioning
confidence: 99%
“…Large amounts of OH can be formed through dissociative recombination of H 3 O + , which in turn is formed through the sequence O + → OH + → H 2 O + → H 3 O + (Maloney et al 1996); as we will report in a forthcoming paper, these molecular ions are indeed detected in absorption from excited levels in both sources. However, both NGC 4418 and Arp 220 have strong X-ray deficits relative to the FIR emission (Maiolino et al 2003;Iwasawa et al 2005). From the X-ray flux reported by Maiolino et al (2003) from NGC 4418, F X (0.3−8 keV) = 1.5 erg s −1 cm −2 , and assuming a point-like X-ray source located at the center of our C core component, the X-ray flux at the surface of C core (r ∼ 10 pc) is ∼0.1 erg s −1 cm −2 ; a similar estimate for Arp 220 with the fluxes reported by Iwasawa et al (2001) yields an X-ray (0.5−10 keV) flux at the surface of the western nucleus (r ∼ 50 pc) of ∼0.5 erg s −1 cm −2 .…”
Section: X-and Cosmic Raysmentioning
confidence: 99%
“…However, only about 30% of AGN are radio-loud (Urry & Padovani 1995). Hard X-rays enabled the discoveries of elusive AGN completely hidden in starburst nuclei (Maiolino et al 2003). However, there exists also a significant fraction of X-ray faint AGN (Wilkes et al 2002), suggesting that also other search techniques should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Fiore et al 2000;Comastri et al 2002;La Franca et al 2005 and references therein). Combining Chandra and archival X-ray data, Maiolino et al (2003) have found that the local total density of AGN may be a factor ∼2 higher than estimated from optical spectroscopic surveys. Up to now the exact proportion of AGN-dominated MIR galaxies is actually not known.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed higher luminosities are typical of AGN activity (see e.g. Ranalli et al 2003;Maiolino et al 2003), while the most X-rayluminous star-forming galaxy known, NGC 3256, has a total X-ray luminosity of L X 8 × 10 41 erg s −1 (Lira et al 2002).…”
Section: X-ray Properties Of the 15 µM Sourcesmentioning
confidence: 99%